Uma posição que se afirma e se respeita no real serviço de Sua Majestade: os militares em Minas Gerais Colonial (1718-1759) - Lívia Nascimento Monteiro; Simone Cristina de Faria (Navigator)
The present text will analyze the acquisition of military patents in the 18th century’s Minas Gerais. Through the work with two different groups - the collectors of the Quintos Reais of Vila do Carmo, who worked between 1718 to 1733; and the Officers of Camara de São João del Rei on duty from 1737 to 1759 – we intend to prove how these positions were fundamental to the local authority and social status on places they lived.